Employee satisfaction and retention:social marketing and happiness - Araceli Galiano-Coronil; Sofía Blanco-Moreno (Retos: Revista de Ciencias de la Administración y Economía)
this research analyses the critical factors influencing employee satisfaction and retention in the context of the Great Resignation by exploring the key organizational elements that significantly impact employee contentment and loyalty. The justification for this study lies in the need for organizations to understand and address the issues leading to high turnover rates and employee dissatisfaction, which have been exacerbated by recent global workforce changes. The main objectives are to identify the key factors that contribute to employee satisfaction and to provide insights into how organizations can enhance their work environments, career growth opportunities, and management practices to retain talent. The methodology involves a semantic network analysis of 138,764 employee reviews from 136 companies, collected via Glassdoor between 2021 and 2023. These reviews were analyzed using the Semantic Networks Tool to identify recurring themes related to work environment, career growth, workload, and management practices. The main results indicate that both current and former employees highly value a supportive and positive work environment and career growth opportunities. However, significant disadvantages include overwork, long hours, and poor management practices. The study highlights that the critical factors influencing employee satisfaction and retention include a positive work environment, opportunities for career growth, and effective management practices